Animated Lands : Studies in Territoriology - Mubi Brighenti, Andrea; Kärrholm, Mattias (Cultural geographies + rewriting the Earth., 2020)
"Andrea Mubi Brighenti and Mattias Kärrholm focus on territory as a "living" thing--and territoriality as an active and constantly reshaping force"--